A performance comparison of photo-fenton decolorization of methylene blue by using bentonite/iron composites prepared by liquid phase and solid phase ion exchange method - Mohammed Jaafar Ali Alatabe; Mohammad Ghorbanpour (Desalination and Water Treatment)
Nowadays, there is a wide range of pollutants present, which requires the treatment of wastewater. The photo-Fenton method has been recognized as valuable in this area. In this study, iron/bentonite composites were created using both liquid phase and solid phase iron exchange techniques, and they were utilized as a photocatalyst for the degradation of methylene blue through photo-Fenton process. Various factors affecting the photocatalytic decolorization were investigated, including the initial concentration of the dye, weight of the catalyst, pH of the solution, and concentration of hydrogen peroxide. The decolorization efficiency of the iron/bentonite composites prepared using the solid phase and liquid phase ion exchange approaches was found to be 99% and 95%, respectively. Based on the data, it can be concluded that the performance of both catalysts was almost equally influenced by the initial dye concentration, catalyst weight, solution pH, and hydrogen peroxide concentration. Moreover, the solid phase ion exchange method demonstrated greater reusability compared to the liquid phase ion exchange method. Consequently, it can be stated that the solid phase ion exchange approach is a suitable and straightforward alternative to the conventional liquid phase ion exchange method for producing a photo-Fenton catalyst.